2010
DOI: 10.4103/0974-8520.82042
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of Nirgundi Ghana Vati and Matra Basti in the management of Gridhrasi with special reference to sciatica

Abstract: Gridhrasi can be equated with sciatica, where pain, weakness, numbness, and other discomforts along the path of the sciatic nerve often accompanies low back pain. It is a common affliction of adults, costing billions of dollars in healthcare and resulting in more lost days of work than any other illness but the common cold. A herniated disc, spinal stenosis, piriformis syndrome, etc., can all cause sciatica. The treatment available for sciatica in modern medicine is not very satisfactory.The role of research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Anuvasana Basti (oil enema) nourishes the dhatus, promotes strength and cures Vata related diseases; Asthapana Basti (decoction enema) cleanses the colon and cures Vata related diseases [18]. Matra Basti is a Nirapada Basti that can be administered conveniently and comfortably for long duration, without complication [11,32]. Matra Basti provides nourishment and strength to the body, and cures Vata related diseases [11].…”
Section: Discussionmentioning
confidence: 99%
“…Anuvasana Basti (oil enema) nourishes the dhatus, promotes strength and cures Vata related diseases; Asthapana Basti (decoction enema) cleanses the colon and cures Vata related diseases [18]. Matra Basti is a Nirapada Basti that can be administered conveniently and comfortably for long duration, without complication [11,32]. Matra Basti provides nourishment and strength to the body, and cures Vata related diseases [11].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies,[ 4 7 ] researchers used Siravyadha to let out Rakta Dhatu along with vitiated Doshas and reported that Siravyadha gives spontaneous relief in the cardinal symptoms of Gridhrasi due to release of impurities or Doshas from the affected area. Similarly in the present study vitiated Doshas along with Rakta Dhatu was let out by pricking with needle on affected area, The vacuum created by the Ghatiyantra helps the vitiated blood to ooze out.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 ] However, in Gridhrasi , as Snayu and Rakta are involved, Agnikarma and Siravyadha (venepuncture) are also the choice of treatment. [ 7 ] The role of simple, safe, economical, and practicable Ayurvedic procedures such as Siravyadha has been studied less in the management of Vatavyadhi such as Gridhrasi . Acharya Sushruta has also mentioned that diseases those are not relieved effectively by Snehana , Lepanadi therapeutic measures, Siravyadha is a management to achieve better and earlier results.…”
Section: Introductionmentioning
confidence: 99%
“…A value of 0.9 was used for R2 to estimate a high level of interaction between covariates: the probability of constipation given the null hypothesis was 0.27, the higher estimate of the prevalence of constipation in adults from a previous review, 28 and the probability of constipation given the alternative hypothesis was 0.45, the incidence of constipation in patients with sciatica in a previous study. 1 …”
Section: Methodsmentioning
confidence: 99%
“…One small study of treatments for radicular sciatica reported that 45% of patients were constipated at baseline. 1 Another study documented a high incidence of constipation in patients after thoracolumbar fusion surgery. 36 A study documenting the disability level of patients with LSS noted that constipation was a common complaint, but this finding was not further investigated.…”
Section: Introductionmentioning
confidence: 99%